PENGARUH MEDIA PEMBELAJARAN JENDELA ILMU TERHADAP HASIL BELAJAR IPS SISWA KELAS V DI SDN TENGGILIS MEJOYO 1 SURABAYA - Ellen Wanodya Ghati (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
Learning success are based on many factors, one of them is teacher, who designing the learning process. The teacher has an opportunity to choose the Learning models, methods, techniques, tactics, strategies, and learning media. Learning media is one of the important aspects that able to affect learning process. It can help teacher and student in learning process, so that, it will determine the result if teacher could choose the media that suitable for the lesson. This article explain about the effect of Jendela ilmu Learning media to social science learning in the fifth grade. This researchment was using two classes, one for control, and one for experiment class. It took place in the fifth grade of Tenggilis Mejoyo 1 Surabaya students. The researchment was began by divided the class into some groups, explained the material, did in the teamwork and then did the Result test. The data was collected from from result test. And it analyzed with t-test. The researchment result showed the using of Jendela Ilmu, able to increase the study result. So that, there is an influence of using Jendela Ilmu learning media in Social Science Learning in fifth grade.